MicroRNA as a biomarker for early detection of amyotrophic lateral sclerosis - Banack, Sandra; Cox, Paul Alan; Dunlop, Rachael (Henry Stewart Talks, 2025)
Parkinson's disease, Amyotrophic lateral sclerosis, Biological markers, Primary lateral sclerosis, MicroRNAs, Extracellular vesicles, Diagnosis